1991
DOI: 10.1121/1.400735
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic spectral shape features as acoustic correlates for initial stop consonants

Abstract: A comprehensive investigation of two acoustic feature sets for English stop consonants spoken in syllable initial position was conducted to determine the relative invariance of the features that cue place and voicing. The features evaluated were overall spectral shape, encoded as the cosine transform coefficients of the nonlinearly scaled amplitude spectrum, and formants. In addition, features were computed both for the static case, i.e., from one 25-ms frame starting at the burst, and for the dynamic case, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…In general, the acoustic attributes that capture the spectral shape of the release burst did better than the acoustic attributes that capture the formant structure. Although many works in the literature, such as [Delattre, Liberman, and Cooper, 1955], [Alwan, 1992], and [Foote, Mashoa, and Silverman, 1993], have emphasized the importance of formant movement, especially the second formant, to the place classification of stop consonants, our results support the findings in [Nossiar and Zahorian, 1991] and [Chen and Alwan, 2000], which state that the shape of the burst spectrum is a more superior cue than the formant movement for classifying stop consonants. A similar conclusion was stated by Ali [2001], who used combinations of acoustic attributes to classify stop consonant and suggested that the role of formant transitions is secondary to the burst spectrum.…”
Section: Summary and Discussionsupporting
confidence: 82%
“…In general, the acoustic attributes that capture the spectral shape of the release burst did better than the acoustic attributes that capture the formant structure. Although many works in the literature, such as [Delattre, Liberman, and Cooper, 1955], [Alwan, 1992], and [Foote, Mashoa, and Silverman, 1993], have emphasized the importance of formant movement, especially the second formant, to the place classification of stop consonants, our results support the findings in [Nossiar and Zahorian, 1991] and [Chen and Alwan, 2000], which state that the shape of the burst spectrum is a more superior cue than the formant movement for classifying stop consonants. A similar conclusion was stated by Ali [2001], who used combinations of acoustic attributes to classify stop consonant and suggested that the role of formant transitions is secondary to the burst spectrum.…”
Section: Summary and Discussionsupporting
confidence: 82%
“…In recent years there has been a growing interest in determining whether speech perception can be viewed as a form of pattern recognition.This approach has yielded several important and successful models (e.g., Nearey, 1997;Nossair & Zahorian, 1991). The present study adds to this body of research by extending a successful model of visual categorization (pattern classification) to the auditory domain.…”
mentioning
confidence: 78%
“…Also, as a step toward understanding the acoustic-auditory restructuring of information, we wished to discover the important acoustic features that distinguish initial stops. In the words of Nossair and Zahorian (1991), who used automatic speech recognition techniques for this purpose, "Such features might be more readily identifiable if the front-end spectral processing more closely approximated that performed by the human auditory system" (p. 2990). Full details of the preprocessing are described elsewhere (Damper, Pont, & E1enius, 1990).…”
Section: Stimuli and Preprocessingmentioning
confidence: 99%